Coefficient Estimates for a New Subclass of Analytic and Bi-Univalent Functions Defined by Hadamard Product. (10th November 2014) - Bulut, Serap
Abstract : We introduce and investigate a new general subclassℋ Σ λ, μ ( φ ; Θ ) of analytic and bi-univalent functions in the open unit diskU . For functions belonging to this class, we obtain estimates on the first two Taylor-Maclaurin coefficients| a 2 | and| a 3 | .